2014
DOI: 10.4161/auto.32136
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress induced by tunicamycin and thapsigargin protects against transient ischemic brain injury

Abstract: Transient cerebral ischemia leads to endoplasmic reticulum (ER) stress. However, the contributions of ER stress to cerebral ischemia are not clear. To address this issue, the ER stress activators tunicamycin (TM) and thapsigargin (TG) were administered to transient middle cerebral artery occluded (tMCAO) mice and oxygen-glucose deprivation-reperfusion (OGD-Rep.)-treated neurons. Both TM and TG showed significant protection against ischemia-induced brain injury, as revealed by reduced brain infarct volume and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
188
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 236 publications
(208 citation statements)
references
References 52 publications
(56 reference statements)
11
188
1
8
Order By: Relevance
“…Recently, mounting evidence indicates autophagy activation is associated with neuroprotection in brain ischemia and crosstalk between the UPR and autophagy plays a critical role in stroke outcome. 30,[38][39][40] For example, in a rat model of ischemic preconditioning, blocking autophagy with 3-methyladenine (3-MA) inhibits GRP78 upregulation, exacerbates ER stress, increases apoptosis, and worsens stroke outcome. 39 Using a rat stroke mode, a significant decrease of p62, indication of autophagy activation, was not observed until 6 h reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mounting evidence indicates autophagy activation is associated with neuroprotection in brain ischemia and crosstalk between the UPR and autophagy plays a critical role in stroke outcome. 30,[38][39][40] For example, in a rat model of ischemic preconditioning, blocking autophagy with 3-methyladenine (3-MA) inhibits GRP78 upregulation, exacerbates ER stress, increases apoptosis, and worsens stroke outcome. 39 Using a rat stroke mode, a significant decrease of p62, indication of autophagy activation, was not observed until 6 h reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that autophagy is decreased by treatment with 4-PBA in acute lung injury [39]. Furthermore, 4-PBA also attenuates transit ischemic brain injury [40]and right ventricular dysfunction during monocrotaline-induced rat Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry pulmonary arterial hypertension [41]. The molecular mechanisms by which ER stress regulates autophagy have been wellcharacterized.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Western blots were done as described previously [14]. The right brain cortex tissues were collected before occlusion or at 12 h after occlusion or reperfusion and were homogenized using RIPA buffer.…”
Section: Western Blot Analysismentioning
confidence: 99%